Implication of Stm1 in the protection of eIF5A, eEF2 and tRNA through dormant ribosomes - Du, Mengtan; Li, Xin; Dong, Wanlin; Zeng, Fuxing (Frontiers in Molecular Biosciences, 2024)
Dormant ribosomes are typically associated with preservation factors to protect themselves from degradation under stress conditions. Stm1/SERBP1 is one such protein that anchors the 40S and 60S subunits together. Several proteins and tRNAs bind to this complex as well, yet the molecular mechanisms remain unclear. Here, we reported the cryo-EM structures of five newly identified Stm1/SERBP1-bound ribosomes. These structures highlighted that eIF5A, eEF2, and tRNA might bind to dormant ribosomes under stress to avoid their own degradation, thus facilitating protein synthesis upon the restoration of growth conditions. In addition, Ribo-seq data analysis reflected the upregulation of nutrient, metabolism, and external-stimulus-related pathways in the ∆stm1 strain, suggesting possible regulatory roles of Stm1. The knowledge generated from the present work will facilitate in better understanding the molecular mechanism of dormant ribosomes.